Judge's consideration of annulment of marriage (Case Study at Yogyakarta Religious Court) - Khairuddin, Khairuddin; Budiarto, Djoko; Erizal, Erizal (Fakultas Hukum Universitas Widya Mataram, 2022)
Marriage is an outer and inner bond between a man and a woman with the ideal goal, to form a happy eternal family based on God Almighty/Supreme, but in fact not all marriages run well according to the purpose of the law. Marriage annulment is a real phenomenon in society, and it does not distinguish any ethnicity, race, religion, or class. The following is a decision study to find out the process of annulment of marriage, in Law Number 1 of 1974 and the judge's considerations in deciding cases of marriage annulment, in the current era although it is only limited to 3 (three) decisions. It is hoped that it will arrive at a final conclusion regarding the judge's considerations on the decision to annul marriage. Keywords: judge's consideration, decision, marriage annulment, petition, lawsuit,